Sweetpotato in diverse economies: Women farmers in Ha Tinh province, Vietnam - Kawarazuka, Nozomi; Bui, Trang (International Potato Center, 2021)
Linking smallholder farmers to markets has been one of the major approaches to improving food security. This approach is often combined with women’s empowerment as well by emphasizing women’s greater involvement in market-oriented agriculture. However, it implicitly undervalues women’s roles in non-market-oriented agriculture and unpaid family labor. This is partly because current mainstream value-chain analyses are premised on a capitalist economy that separates production from the non-capitalist form of all activities. The aim of this study is to gain a more nuanced understanding of non- or less-market oriented agricultural activities led by women farmers and the oft-neglected value of these activities in rural households. The study employs the concept of diverse economies which consider non-market-oriented activities as part of various economic systems, including subsistence farming, exchange of food, and exchange of labor. A case study was conducted in a community in the Ha Tinh province in Vietnam in April 2021, when COVID-19 had little impact on agriculture. Findings show that women manage non-market-oriented sweetpotato production, which is central to maintaining a local seed system, a reciprocal support system, and livestock production. Furthermore, women choose the best varieties of sweetpotato and use their own social networks for obtaining planting materials and distributing the sweetpotato harvest, enabling women to control both agricultural production and the distribution of benefits. In this context, shifting to commercial agriculture is not a desired form of agricultural development for women. Interventions in agricultural value chains require careful considerations of women’s aspirations and household strategies embedded in broad production and reproduction within extended and intergenerational family relations.